Boriding kinetics and mechanical behaviour of AISI O1 steel. (August 2015) - Elias-Espinosa, M.; Ortiz-Domínguez, M.; Keddam, M.; Gómez-Vargas, O. A.; Arenas-Flores, A.; Barrientos-Hernández, F. R.; West, A. R.; Sinclair, D. C.
Abstract : In this work, American Iron and Steel Institute (AISI) O1 steel was pack borided in the temperature range of 1123–1273 K for treatment times between 2 and 8 hours. A kinetic model was proposed for estimating the boron diffusion coefficients through the Fe2 B layers. As a result, the boron activation energy for the AISI O1 steel was estimated as 197·2 kJ mol − 1 . This value of energy was compared to the literature data. In addtion, to extend the validity of the present model, two additional boriding conditions were done. The Fe2 B layers grown on AISI O1 steel were characterised by use of the following experimental techniques: scanning electron microscopy, X-ray diffraction analysis and Daimler-Benz Rockwell-C indentation technique. Finally, the scratch and pin on disc tests for wear resistance were respectively performed using an LG Motion Ltd and a CSM tribometer under dry sliding conditions.